Occurrence, spatial distributions, and ecological risk of pyrethroids in coastal regions of South Yellow and East China Seas. (June 2022) - Cao, Shengkai; Zhang, Peng; Cai, Minghong; Yang, Yan; Liu, Yanguang; Ge, Linke; Ma, Hongrui
Abstract: Pyrethroids are increasingly receiving attention as aqueous micropollutants, but their presence has been reported only in a few small coastal areas. In this study, we investigated the distribution, sources, and risks of nine pyrethroids in large marine zones. The 40 seawater samples were collected from the South Yellow Sea (SYS) and East China Sea (ECS) in China, during the spring of 2020, using a high-volume, solid-phase extraction method. The total pyrethroid concentrations ranged from 0.72 to 1.82 ng L −1 in the SYS and from 0.02 to 11.0 ng L −1 in the ECS. We used cluster analysis to classify pollutant sources into five categories, and discussed the influence of sources on the transport and distribution of pyrethroids in each group. Ecological risk assessment indicated that pyrethroids pose a high risk to crustaceans and a negligible risk to others. These results are important for understanding the behavior of pyrethroids in marine environments. Graphical abstract: Unlabelled Image Highlights: Efficient Hi-throat/Hi-volume SPE was used to concentrate pyrethroids from seawater. Occurrence of nine pyrethroids was investigated at South Yellow and East China Seas. Distribution and sources are influenced by both human activities and ocean currents. Ecological risk assessment indicated that pyrethroids pose a high risk to crustaceans.